2018
DOI: 10.1016/j.jtho.2018.08.244
|View full text |Cite
|
Sign up to set email alerts
|

OA02.07 Updated Results of Phase 1 Study of DS-8201a in HER2-Expressing or –Mutated Advanced Non-Small-Cell Lung Cancer

Abstract: and 40 patients were evaluated for response. 65.1% of patients had received at least two prior lines of therapy for metastatic disease. 60% of patients had grade 3 adverse events; most common were skin-rash (27.5%) and diarrhea (12.5%). 45.0% of patients required dose reduction to 12mg, while 17.5% required dose reduction to 8mg. One patient stopped treatment due to grade 3 skin rash. ORR at eight weeks was 58% (95%-CI 40.9-73.0) and the DCR was 90% (95%-CI 76.3-97.2). Among 23 patients who achieved partial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The combination of dabrafenib (a BRAF TKI) and trametinib (a MEK TKI) is the SoC treatment according to the FDA and EMA in patients with BRAF V600E-mutant NSCLC regardless of prior treatment, 114,115 as BRAF TKI monotherapy has been reported to have limited efficacy, such as in AcSé trial (RR ¼ 45%, PFS ¼ 5.2 months, and OS ¼ 9.3 months [ Table 6]). [114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] The recent functional classification of BRAF mutations (class I, V600 mutations; class II, non-V600 mutations; and class III, ERK-signaling amplification) demonstrated that class II and III tumors have unfavorable prognosis and suggested that class-specific therapies are necessary. 133 BRAF-mutant NSCLC overlaps with PD-L1 expression in 60% of cases (45% with PD-L1 expression !50%), low or intermediate TMB, and microsatellite-stable status, 134 but ICI efficacy is similar to that in patients with wild-type BRAF.…”
Section: Advances In Other Genomic Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of dabrafenib (a BRAF TKI) and trametinib (a MEK TKI) is the SoC treatment according to the FDA and EMA in patients with BRAF V600E-mutant NSCLC regardless of prior treatment, 114,115 as BRAF TKI monotherapy has been reported to have limited efficacy, such as in AcSé trial (RR ¼ 45%, PFS ¼ 5.2 months, and OS ¼ 9.3 months [ Table 6]). [114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] The recent functional classification of BRAF mutations (class I, V600 mutations; class II, non-V600 mutations; and class III, ERK-signaling amplification) demonstrated that class II and III tumors have unfavorable prognosis and suggested that class-specific therapies are necessary. 133 BRAF-mutant NSCLC overlaps with PD-L1 expression in 60% of cases (45% with PD-L1 expression !50%), low or intermediate TMB, and microsatellite-stable status, 134 but ICI efficacy is similar to that in patients with wild-type BRAF.…”
Section: Advances In Other Genomic Alterationsmentioning
confidence: 99%
“…138 DS-8201a is a new HER2-targeting antibody-drug conjugate incorporating a novel topoisomerase I inhibitor. In HER2-mutant patients, it gave a clinically significant RR of 73% and a median PFS of 14.2 months 125 ; and a phase II trial (NCT03505710) is ongoing (see Table 6).…”
Section: Advances In Other Genomic Alterationsmentioning
confidence: 99%
“…Poziotinib showed promising preclinical and early clinical activity in NSCLC patients with HER2 or EGFR exon 20 ins,105 in an ongoing phase II study (NCT03066206), initial responses of 50% and a median PFS of 5.1 months were observed in 12 evaluable advanced HER2 exon 20 ins NSCLC patients 106. An ongoing phase I study of another novel HER2-targeted drug, trastuzumab deruxtecan (DS-8201a), demonstrated an ORR of 62.5% and DCR of 75% in 12 patients with HER2-expressing or -mutated NSCLC 107. A phase II study for this drug against the same condition recently began accrual (NCT03505710).…”
Section: Her2 Mutationmentioning
confidence: 99%
“…Subsequent expansion of the NSCLC cohort ( n = 18) reported confirmed response rate of 58.8% (10 of 17 patients). The median duration of response was 9.9 months, and grade 3 or higher toxicities were reported in 25% of patients with one patient death because of interstitial lung disease (Table 2) . The response rate in patients with confirmed ERBB2 mutations was 72.7% (8 of 11 patients), and median duration of response was 11.9 months.…”
Section: Introductionmentioning
confidence: 99%